Pengaruh Rekrutmen, Seleksi, Dan Penempatan Terhadap Kinerja Pegawai Dengan Komitmen Organisasional Sebagai Variabel Intervening di Dinas Lingkungan Hidup Kabupaten Situbondo - Dariawanto, Echwan; Gustina Pane , Sri; Puspa , Tiara (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2026)
This study was conducted at the Environmental Agency of Situbondo Regency. This study analyze the influence of recruitment, selection, and placement on employee performance, with organizational commitment as an intervening variable. The research was motivated by inconsistencies in previous findings regarding the impact of these three variables on employee performance, as well as the importance of improving employee performance in government institution, particulary at the Environmental Agency of Situbondo Regency, which still faces various challenges in public service. This study utilizes a quantitative approach through an explanatory research method to assess the relationships between variables. This study involved 131 civil servants from the Environmental Agency of Situbondo Regency, selected through a non-probability sampling technique. The data were processed using Structural Equation Modeling (SEM) supported by AMOS 23 and SPSS 21. The findings showed that recruitment significantly improved employee performance. In contrast, selection and placement did not demonstrate a direct effect. However, when organizational commitment acted as a mediating variable, both selection and placement exhibited a significant positive influence on performance. Additionally, organizational commitment itself was proven to enhance employee performance significantly. Theoretically, these findings reinforce human capital and social exchange theories and provide a reference for future reseach. Practically, the study suggest that the Environmental Agency of Situbondo Regency should provide input to relevant personnel agnecies to improve recruitment, selection, and placement processes as part of effort to enchance employee performance. Future researcher are advised to incorporate additional variables that may influence employee performance and expand the scope to the provincial government level.